MCSimulRisk: an Educational Tool for Quantitative Risk Analysis. - Acebes Senovilla, Fernando; Curto, David; González-Varona, José Manuel; Pajares, Javier (ARGESIM, 2024)
MCSimulRisk (Monte Carlo Simulation for Risk Analysis) is an application developed in MATLAB for Monte Carlo Simulation and quantitative risk analysis. In the Master's Degree in Project Management at the University of Valladolid, "Risk Management" is taught. Quantitative risk analysis is an essential part of teaching this subject. In the last few courses, students have used commercial applications that allow Monte Carlo Simulation in this subject. To correct the problems detected while students did laboratory exercises, we decided to develop this educational tool with the following main objectives: (1) allow students to efficiently carry out Monte Carlo Simulation for any project network, regardless of its complexity; (2) easily integrate different types of uncertainty (aleatoric, stochastic and epistemic) that can impact project objectives into the model. In addition to the above, this tool should help research tasks by extending research lines not yet addressed in the literature to integrate distinct types of uncertainty.
https://www.sne-journal.org/aims-and-scope
Keywords: Gestión del riesgo; Quantitative risk analysis; Project management; Monte Carlo simulation; Risk management